Evaluation of Customer centered approaches adapted in Public Sector Organizations - Selvarajan, P. (University of Sri Jayewardenepura, 2009)
This research study focuses on identifying how far the public sector organizations which deal with public in higher level understand the needs of them in a correct manner and provide services appropriately. In the present world, every organization wants to provide efficient services through its various activities to survive and thrive in the market. But in case of public sector organizations (except banks) they usually do not concentrate on this aspect as they are functioning like monopolies. However in people’s point of view most of the public frequently visit to the public sector organization rather than private sector to accomplish their tasks and fulfill their needs. In this manner they face many difficulties and delays when they want to accomplish a particular work in public sector organizations. This will create the misunderstanding of public on the employees of the organizations and affect the organization’s good will and leads to public dissatisfaction. In order to reduce defects and create a good rapport among them, the author has selected three different sectors which have higher public dealings namely District Secretariat (Kachcheri) Department of Education (especially schools) and the Health service (Hospital and allied organizations) in Vavuniya district. Primary data were collected from various sources for this research and the author has found how efficiently the public sector organizations stated above provide their service to public in this district; the gap between the actual performance and the estimated efficiency and recommended appropriate customer - centered approaches to bridge the gap among these organizations.
Keywords: Customer-Centered approach; Public sector organizations; Rapport; Public dissatisfaction